The relationship between leadership and organisational effectiveness among indigenous banks in Kenya - Muriithi, Samuel Muiruri (Rhodes University, Faculty of Commerce, Department of Management, 2015)
Defining leadership effectiveness (LE) remains a controversial subject with scholars and researchers disagreeing on a common definition. Most studies term leadership effectiveness as the leaders' ability to successfully exercise personal influence and abilities in order to accomplish set standards. Such leadership effectiveness was measured using three elements, namely influence, follow commitment and versatility. To be effective, leaders must possess certain competencies and perform specific tasks (independent variables). In this study, three leadership competencies, namely strategic thinking, emotional effectiveness and transformational leadership were examined. Similarly, seven leadership tasks (set organisational direction, develop human capital, build core competencies, create organisational alignment, sustain appropriate organisational culture, manage change and establish balanced organisational control) were identified as essential for the attainment of leadership effectiveness (intervening variable) which, in turn, leads to organisational effectiveness (dependent variable). Given the importance of leadership effectiveness to organisational effectiveness, the purpose of this study was to identify, investigate and empirically test the possible relationship between leadership effectiveness and organisational effectiveness within the Kenyan indigenous banks. To achieve the aim of the study, a survey was undertaken using a structured self-administered questionnaire. The respondents were identified using both probability and non-probability techniques with the survey yielding 257 usable questionnaires that were statistically analysed. The proposed hypothetical relationship between leadership effectiveness and organisational effectiveness was assessed using Structural Equation Modelling (SEM), a multivariate statistical technique. The SEM included Cronbach's alpha and confirmatory factor analyses to assess the dicriminant reliability and validity of the measuring instrument, and Goodness-of-fit indices. The study findings demonstrated the existence of a strong relationship between leadership competencies, tasks performed and leadership effectiveness which in turn impacts on organisational effectiveness, in this case the overall effectiveness of the Kenyan indigenous banks.
Keywords: Leadership -- Kenya; Organizational effectiveness -- Kenya; Transformational leadership -- Kenya; Strategic planning -- Kenya; Community banks -- Kenya; Structural equation modeling; Emotional intelligence